Protective Effect of Celecoxib on Early Postoperative Cognitive Dysfunction in Geriatric Patients - Zhu, Yangzi; Yao, Rui; Li, Yan; Wu, Congyou; Heng, Lei; Zhou, Meiyan; Yan, Li; Deng, Yan; Zhang, Zhe; Ping, Lei; Wu, Yuqing; Wang, Shengtao; et al. (Frontiers in Neurology, 2018)
Objective: Inflammation plays a key role in the etiology and pathology of postoperative cognitive dysfunction (POCD). Cyclooxygenase (COX)-2 inhibitor celecoxib is used for the treatment of acute pain due to its potent anti-inflammatory and analgesic effects. Herein, we evaluated the effects of celecoxib on POCD in geriatric patients. Methods: A total of 178 geriatric patients undergoing total knee arthroplasty were randomly divided into two groups and treated with celecoxib (group C) or placebo (group P). The levels of perioperative plasma COX-2, IL-1β, IL-6, TNF-α, neuron-specific enolase and S100β were detected in all patients. The pain intensity was measured by numerical rating scale (NRS). A battery of 9 neuropsychological tests was performed pre-operatively and 1 week, and 3 months postoperatively. Patients, whose postoperative performance declined by≧1 standard deviation as compared to each preoperative test score on ≧2 tests, were classified as POCD. Results: A significant decrease in POCD incidence was found in group C as compared to group P on postoperative day 7 (12.3% vs. 34.1%; p<0.05). POCD incidence did not differ between the two groups at the 3-month follow-up (8.8% vs. 9.7%). NRS scores at days 3 and 4 post-surgery were significantly lower in group C (p<0.05). Patients in group C showed lower level of plasma COX-2, IL-1β, IL-6, TNF-α and S100β as compared to group P postoperatively (p<0.05). Conclusion: These results demonstrated that celecoxib can decrease early POCD incidence after total knee arthroplasty in geriatric patients, which might be mediated by suppressing inflammation and acute postoperative pain caused by surgical trauma.